Kenji Mizoguchi's Fallen women = Yoru no onnatachi - Hisaita, Eijirō 1898-1976; Ohzawa, Hisato 1907-1953; Hisaita, Eijirō 1898-1976 (<<The>> Criterion Coll., 2008)
[v. 1]. Osaka elegy. Switchboard operator Ayako agrees to enter into an affair with her married boss after he promises to support her and her father - setting her off on a seemingly irreversible downward spiral
Bildformat 1.33:1
Orig.: Japan 1948
Keywords: Frau; Weltkrieg (1939-1945); Adultery -- Japan -- Drama; Brothels -- Japan -- Tokyo -- Drama; Feature films; Geishas -- Japan -- Kyoto -- Social conditions -- Drama; Man-woman relationships -- Japan -- Drama; Prostitutes -- Japan -- Drama; Prostitutes -- Japan -- Tokyo -- Drama; Red-light districts -- Japan -- Tokyo -- Drama; Sexual harassment -- Japan -- Drama; Sisters -- Japan -- Kyoto -- Drama; War widows -- Japan -- Drama; Women -- Japan -- Kyoto -- Social conditions -- Drama; World War, 1939-1945 -- Civilians -- Drama